Self-regulated learning: theoretical frameworks to support in scientific education (Research, Society and Development, 2020)
The present text addresses self-regulated learning as defined by Zimmerman, extending the discussion to the development of new theoretical frameworks. The objective is to promote a review on the topic and provide a theoretical framework to support didactic actions toward this purpose. More specifically, the text highlights elements that may support the structuring of didactic proposals (or sequences) in the field of scientific education, and that favor this type of learning as reference. The study is characterized as bibliographic research in which works related to the theme were consulted. As a result, it is inferred the importance of teachers to structure didactic actions based on the three moments that constitute the model proposed by Zimmerman (anticipation and preparation; execution and control; and self-regulation). Such moments are grounded on cognitive, metacognitive, and motivational aspects that stand out in maximizing academic performance, especially in the field of scientific education.